A Study on the Applications of Negacyclic Matrices in the Construction of Hadamard Matrices - Manjhi, Pankaj Kumar; Kujur, Ninian Nauneet (Communications in Mathematics and Applications, 2023)
This article deals with the proper placement of negacyclic matrices as block matrices in a matrix so as to construct a Hadamard matrix. The article contains many new examples of suitable negacyclic matrices of such type with some new observations. The article also includes some negative results.
Keywords: Hadamard matrix; Negacyclic matrix; Circulant matrix; Orthogonal design